PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF MENGGUNAKAN APLIKASI VN PADA PEMBELAJARAN TEMATIK TEMA INDAHNYA KEBERSAMAAN MENGGUNAKAN MODEL KONTEKSTUAL DI KELAS IV SD - Surya Amalia; Beta Rapita Silalahi (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This study aims to develop interactive learning video media and to determine the feasibility of interactive video media using VN applications in thematic learning on the beautiful theme of togetherness using a contestual model, which is valid from the results of feasibility validation by material experts, media experts and teacher responses. This research is a type of Research and Development (R&D) research with the ADDIE model which includes five steps, namely: stages of analysis, design, development, implementation, and evaluation. But this research only limits it to three stages, namely only to the development stage. The subjects in this study are material expert validators, media experts and learning experts. The instrument used to collect data is a questionnaire. The data analysis techniques used are qualitative and quantitative descriptive analysis techniques. The media developed was validated by one material expert, one media expert and one grade IV elementary school teacher. Based on the assessment of validation results by media experts, produce interactive video products with a percentage value of 90% (very feasible). Based on the assessment of the validation results by material experts, it produces interactive video products with a percentage of 82.5% (very feasible) and based on the